Alexander Campbell (1822-1892): The Travails of a Father of Confederation - Martin, Ged (Ontario History)

(untitled) (The Ontario Historical Society, 2013)
Although he was a father of Confederation, Alexander Campbell (1822-1892) is generally overshadowed by John A. Macdonald, whose law partner he was from 1843 to 1849, and whom he served for the first twenty years of the Dominion as Conservative party leader in the Senate, before retiring to become Lieutenant-Governor of Ontario in 1887. In fact, Campbell’s participation in public life was an achievement, since he suffered from impairment of mobility and was also subject to epileptic attacks. His marriage in England in 1855 to Frederica Sandwith broke up when she returned to Europe in 1871. She was later certified as insane and spent several years in asylums. Victorian reticence generally prevented open allusion to the difficulties of Campbell’s private life. The accidental death by shooting of his younger son in 1886, initially interpreted as suicide, prompted a few journalists to lift the veil and provide clues which this article traces back into the sparse archival record.